Comparisonal Analysis Of Customer Satisfaction Towards JNE And J&T Package Delivery Services, Makale City, Tana Toraja Regency - Chrismesi Pagiu; Rati Pundissing (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this research is to compare customer satisfaction with package delivery services at JNE and J&T Makale City in Tana Toraja Regency. This research utilizes a descriptive quantitative research method. A questionnaire was issued to consumers of JNE and J&T as part of the data collection technique. There were a total of 1,085 participants in this research, including 300 JNE customers and 785 J&T customers. Using the Slovin formula, the researchers drew the same number of samples from the whole population in each site, up to 75 people. The Customer Satisfaction Index (CSI) was used for data analysis in order to calculate the expected level of product or service qualities based on an analysis of total customer satisfaction. The results showed that J&T consumers were more satisfied with the delivery services than JNE customers, Therefore, the trustworthiness of the services offered by the Makale City JNT must be enhanced, J&T must increase the service quality in terms of assurances and physical evidence, as well as their responsiveness and sensitivity.